Identification of main agronomic characteristics and screening of elite germplasm resources of the cotton after rape cultivation in the Yangzte River Basin - DENG Yanfeng; XIAO Shuiping; YANG Shaoqun; LIU Xinwen; KE Xingsheng; WANG Tao; YANG Xiu (浙江大学学报. 农业与生命科学版)
In order to expand the germplasm resource bank of cotton after rape cultivation in the Yangtze River Basin, screen out excellent germplasm suitable for hybrid parents, and improve the efficiency of cotton breeding, 11 main agronomic traits of 72 upland cotton materials introduced were analyzed with the methods of variability, correlation analysis, principal component analysis and clustering analysis by statistical software SAS V8. The results showed that, the 72 Gossypium hirsutum germplasm resources had rich genetic diversity, and the variation coefficients of characters among 72 materials ranged from 1.15% to 30.31%. The variation coefficient of boll number per plant was the largest, was 30.31%. The correlation analysis showed that the growth period was significantly and positively correlated with plant type traits. The plant height was extremely significantly and positively correlated with the boll mass. The number of fruit branches per plant was extremely significantly and positively correlated with the boll number per plant, and significantly and negatively correlated with the boll mass. The lint percentage and boll mass were significantly and negatively correlated with some quality traits. The principal component analysis showed that the cumulative contribution rate of the first four principal components was 73.98%, which including most information of 11 traits. Clustering analysis showed that the 72 cotton materials were classified into six groups. Group Ⅰ belonged to high-quality materials, and group Ⅱ belonged to high-yield materials. Group Ⅴ belonged to high-yield and high-quality materials, which could be used in breeding. Two high-quality cotton materials and six high-yield cotton materials were screened out with the method of comprehensive evaluation, which would be used to cultivate new materials with combination of yield and quality traits.